The hedgehog inhibitor GANT61 sensitizes prostate cancer cells to ionizing radiation both in vitro and in vivo - Gonnissen, A; Isebaert, S; McKee, C; Dok, R; Haustermans, K; Muschel, R (Impact Journals, 2016)
Limited data exists regarding the combination of Hedgehog signaling (Hh) inhibition and radiotherapy, even though there are several indications that this might be a promising treatment strategy. In this study, we evaluated the combination of two Hh inhibitors, the SMO inhibitor GDC-0449 and the GLI inhibitor GANT61 with radiotherapy in different prostate cancer (PCa) models. In vitro, GANT61 was able to sensitize 22Rv1 PCa cells but not PC3 and DU145 PCa cells. The lack of radiosensitization in the latter cell lines was shown to be dependent on the presence of mutated p53. Introduction of WT p53 into PC3 cells resulted in radiosensization following GANT61 treatment, suggesting that the p53 transcription factor plays an important role in the GANT61-induced radiosensitization in vitro. Targeting at the level of SMO (GDC-0449) did not show cytotoxicity or synergy with radiation. Furthermore, we confirmed the radiosensitization effect of GANT61 in two in vivo xenograft PCa models. The decrease in tumor growth was associated with decreased proliferation and increased apoptosis. In conclusion, we provide evidence that GANT61 in combination with radiation treatment might represent a promising therapeutic strategy for enhancing the radiation response of PCa patients.